Electroactive poly(vinylidene fluoride – trifluorethylene) (PVDF-TrFE) microporous membranes for Lithium-ion battery applications - Costa, Carlos M. (2012)
Poly(vinylidene fluoride-trifluorethylene) porous membranes were prepared by solvent evaporation at room temperature. The morphology of the membranes reveals an interconnected porous structure with porosity ranging from 72% up to 80%. The conductivity of the membranes and the LiClO4 uptake increases with increasing porosity. After uptake, the increase of the electrical conductivity is larger for the less porous membranes and the thermal stability of the electrical conductivity is increased.